Exploring the Role of Symbolic Convergence Theory in Enhancing Group Cohesiveness and Decision Making: A Systematic Literature Review Study - Pratiwi, Tiara Hana; Purba, Eva Martina; Irwansyah, Irwansyah (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Symbolic Convergence Theory describes group cohesiveness and decision-making influenced by symbolic convergence and rhetorical vision because they affect how group members understand and share common social values. This research aims to provide an overview of the implementation of Symbolic Convergence Theory in group communication, especially in cohesiveness and group decision-making. This research uses the Systematic Literature Review (SLR) method. This research systematically identifies and evaluates group cohesiveness and decision-making in several previous studies. However, along with the development of time and technology, direct and analog communication began to be less researched. Keywords: Symbolic Convergence Theory, group, cohesiveness, decision-making